Time-use Agency - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Time allocations display highly gendered patterns across the globe. Women experience much higher levels of time poverty due to the disproportionate share of care and domestic work they bear. The standard time-use modules allow us to understand how individuals allocate their time across different activities. But they are silent on individuals’ preferences regarding such allocations. This tool aims to measure time-use agency, defined as the confidence in and the ability to make an act upon strategic choices about how to allocate one’s time. This data study includes following files. 1. A survey document (including implementation guidelines)